Emission of Volatile Organic Compounds to the Atmosphere from Photochemistry in Thermokarst Ponds in Subarctic Canada - Fillion, Daniel; Perrier, Sébastien; Riva, M.; George, C.; Domine, Florent; Couture, Raoul-Marie (ACS Earth and Space Chemistry, 2024)
International audience Climate warming is accelerating the thawing of permafrost, which contains almost twice as much carbon as the atmosphere, to a point where a large quantity of dissolved organic matter (DOM) is being mobilized toward surface waters, including thermokarst ponds. DOM can be partially photodegraded into volatile organic compounds (VOCs), which are little studied in Arctic environments. The main objective of this work is to identify and quantify the VOCs emitted to the gas phase by photochemistry from thermokarst water sampled in four ponds from two study sites in northern Quebec. VOC emissions were characterized by proton-transfer reaction mass spectrometry. Results show rapid photoproduction of between 35 and 59 VOCs when DOM water samples are exposed to radiation. Our results also show that the quality of DOM is a more important factor to control VOC photoproduction than the quantity of DOM. Depending on the assumptions used in upscaling our laboratory results to the field sites, calculations yield net carbon fluxes between 1.93 and 174 μmol C m–2 d–1. While these values are small compared to literature values of CO2 and CH4 fluxes from thermokarst ponds, this process represents an important flux of reactive molecules that could affect Arctic atmospheric chemistry.